Youth Characteristics and Internet Addiction in the Eastern Mediterranean Region: The Mediating Role of Social Anxiety Disorder. - Elrewany, Ehab; Ghazy, Ramy Mohamed; Shiba, Hoda Ali Ahmed; Abdel-Rahman, Suzan; Shabrawy, Abdelhamid El; alabdo, Nayef kheder; Altayf, Alhasan; Alshahrani, Fahad Abdullah S.; Abouelmagd, Moaz Elsayed; Tarawneh, Haneen; Al-Muqbel, Rahaf; Fadl, Noha (International Journal of Mental Health & Addiction, 2026)
This study aimed to investigate the mediating role of social anxiety in the association between Internet addiction and characteristics of youth in the Eastern Mediterranean Region. A cross-sectional study included 2095 youth aged 15–24 from five countries (Saudi Arabia, Libya, Jordan, Egypt, and Syria). The outcome was Internet addiction; the independent variables were characteristics of youth; meanwhile, the mediator was social anxiety. The Arabic versions of the Compulsive Internet Use Scale and the Social Phobia Inventory were used to assess Internet addiction and social anxiety, respectively. The mean age of participants was 20.8 ± 2.5 years, and 46.8% were males. The prevalence of Internet addiction and social anxiety was 43.3% and 67.5%, respectively. The structural equation modelling showed that social anxiety was positively associated with Internet addiction. Urban residents, older age, and males were less likely to develop Internet addiction, the associations were both direct and indirect through social anxiety. Participants from higher-income countries were less likely to report Internet addiction compared to low-income countries; the mediating role of social anxiety reversed this association. These findings highlight the importance of reducing social anxiety to minimize the susceptibility of youth to Internet addiction.